Sweetgum: a new look - Adams Joshua P; Lingbeck Jody M; Crandall Philip G; Martin Elizabeth M; O’Bryan Corliss A (iForest - Biogeosciences and Forestry, 2015)
Sweetgum (Liquidambar styraciflua L.) is the only species of its genus in the Western hemisphere. The species is a relatively early successional species with wide seed dispersal, fast growth and is considered one of the most adaptable tree species in North America, growing across a wide range of soil types, altitudes, and hydrologic conditions. This species has routinely been considered a lesser desired species by many forest managers trying to grow tree plantations or even in natural stands because the species tends to rapidly invade and dominate a site. However, because of sweetgum’s adaptability, ease of propagation and field planting, and fast growth rate, the tending of sweetgum as a potential crop for improved markets has been reinvigorated. Managing sweetgum also opens the possibility of development of new products and markets that supplement the traditional markets and can produce further value-added products. Increasingly, sweetgum is not viewed with as much antipathy amongst foresters and its potential as valuable resources is being rediscovered.